TANGGUNG JAWAB PELAKU USAHA DAN SANKSI HUKUM TERHADAP PELAKU USAHA YANG MENJUAL PRODUK REKAYASA BERAS OPLOSAN - Wawan Fransisco (LPPM UNIVERSITAS BINA INSAN, 2019)
MaiFood is a basic human need and its fulfill is a part of human rights. The food must always be available every time, and it should be in good quality, nutritious and the price should be affordable to the community. Certain system, which protect the producers and the consumers. is needed for reaching the fulfillment. In fact, there are some producers who conduct fraud in food business, namely by adding the chlorine to the food. This additive contain may harm the human health, so that food does not meet food quality standards. Based on above mentioned problems, this article will focus on the impact of the contaminated food for the health of consumers and the responsibility of the producers against loss suffered by consumers due to consumption of food (rice ) chlorine-containing materials. The impact of consuming food (rice), may cause cardiovascular disease, atherosclerosis, anemia, high blood pressure. The producers shall take responsibility by paying restitution to the consumer and the consumers do not need to prove the fault.